Extended Stability Evaluation of Selected Cathinones - Ciallella, Heather L.; Rutter, Lexus R.; Nisbet, Lorna A.; Scott, Karen S. (Frontiers in Chemistry, 2020)
Understanding the stability of drugs in a forensic toxicology setting is critical for the evaluation of drug concentrations. Synthetic cathinones are new psychoactive substances structurally derived from cathinone, the psychoactive component of Catha edulis (“khat”), a shrub that is indigenous to the Middle East and East Africa. Previous research has evaluated the stability of synthetic cathinones in biological matrices, including blood preserved with the combination of NaF and K2C2O4 used in grey-top tubes. However, it does not assess their stability in blood preserved with Na2EDTA, used for some clinical samples. Further, stability in unpreserved urine samples was only studied for two weeks. This research evaluates the stabilities of four Schedule I synthetic cathinones: mephedrone, MDPV (3,4-methylenedioxypyrovalerone), naphyrone, and α-PVP (alpha-pyrrolidinopentiophenone) at 21 oC (room temperature), 4 oC (refrigerator), and -20 oC (freezer). Stability was assessed in methanolic and acetonitrile solutions, as well as in Na2EDTA-preserved blood and unpreserved urine. Solutions (1 mg/L) of each drug in each matrix stored in aliquots (100 μL, solvents; 1.2 mL, biological samples; n=12) at each of the three temperatures for triplicate analysis on days 3, 7, 14, and 30. On day 0 of each study, three additional aliquots of each solution were analysed. Biological samples underwent solid-phase extraction before analysis. All samples were analysed in full-scan by gas chromatography-mass spectrometry (GC-MS). The results of this study show that under room temperature and refrigerator storage conditions, mephedrone, naphyrone, and MDPV will degrade in methanol, this degradation starts are early as day three. Additionally, all four drugs will degrade in Na2EDTA-preserved human whole blood samples in at least one evaluated storage environment. However, when in acetonitrile-based working solutions and unpreserved urine samples, they proved to be more stable. Methanolic working solutions and samples of Na2EDTA-preserved blood containing these cathinones should be stored in the freezer and used or tested with urgency to ensure that quantitative sample analysis is as accurate as possible in forensic casework.